2010
DOI: 10.1111/j.1600-0706.2010.18573.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition and the assembly of light‐limited phytoplankton communities

Abstract: Photoinhibition is characterised by a decreasing rate of photosynthesis with increasing light. It occurs in many photosynthetic organisms and is especially apparent in phytoplankton species sensitive to high light. Yet, the population and community level consequences of photoinhibition are not well understood. Here, we present a resource competition model that includes photoinhibition. The model shows that, in strong light, photoinhibition leads to an increase of the specific growth rate with increasing popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 65 publications
0
53
1
1
Order By: Relevance
“…Our previous in situ study conducted from March to April (dry season) revealed the presence of photoinhibition in Lake Dianchi (Zhou et al 2015b). In the present study, low phytoplankton biomass was detected during the SHs of the dry season (with a relative increase in SHs and a lower bloom biomass compared to the rainy season), which might have resulted from less self-shading and more photoinhibition (Gerla et al 2011).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Our previous in situ study conducted from March to April (dry season) revealed the presence of photoinhibition in Lake Dianchi (Zhou et al 2015b). In the present study, low phytoplankton biomass was detected during the SHs of the dry season (with a relative increase in SHs and a lower bloom biomass compared to the rainy season), which might have resulted from less self-shading and more photoinhibition (Gerla et al 2011).…”
Section: Discussioncontrasting
confidence: 40%
“…These results indicated that the SHs were sufficient for phytoplankton growth in the low-latitude plateau region of Lake Dianchi, which features a relatively high level of solar radiation and a predominance of cyanobacteria with gas vesicles ). An exceedingly high light intensity induces algal photoinhibition, and a low population density does not allow for sufficient self-shading for protection (Gerla et al 2011). Our previous in situ study conducted from March to April (dry season) revealed the presence of photoinhibition in Lake Dianchi (Zhou et al 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, eruptions present unique opportunities for scientific discovery though such studies are often hindered by a lack of pre-eruption and post-eruption data that allow comprehensive assessment of their effects and the mechanisms of those outcomes (Lindenmayer et al 2010;Larson 2011). Past studies of the effect of eruptions on aquatic ecosystems have emphasized fertilization by ash-borne elements such as phosphorus and iron (Hamme et al 2010;Lin et al 2011). Studies in marine environments have shown that, after volcanic eruptions, the concentrations of chlorophyll, as a proxy of phytoplankton biomass, increase (Hamme et al 2010;Lin et al 2011).…”
mentioning
confidence: 99%
“…Past studies of the effect of eruptions on aquatic ecosystems have emphasized fertilization by ash-borne elements such as phosphorus and iron (Hamme et al 2010;Lin et al 2011). Studies in marine environments have shown that, after volcanic eruptions, the concentrations of chlorophyll, as a proxy of phytoplankton biomass, increase (Hamme et al 2010;Lin et al 2011). Paleolimnological evidence from a lake in Iceland also shows that, after a volcanic eruption that deposited considerable amounts of tephra, there was an increase in chlorophyll-derived pigments in sediments, indicating an increase in phytoplankton biomass following volcanic ash deposition (Einarsson et al 1993).…”
mentioning
confidence: 99%
“…In a two-species community such as ours, the species stably coexist when each species can invade (1) an equilibrium density of the other (11), and the species are alternative stable states when neither can invade (2) an equilibrium density of the other (2 2), while (1 2) or (2 1) leads to competitive exclusion of the species that cannot invade (e.g., Gerla et al 2011). In the case of alternative stable states, the species that establishes first outcompetes the other.…”
Section: Analysis Methodsmentioning
confidence: 99%